FAKTOR-FAKTOR YANG MEMPENGARUHI ANEMIA PADA IBU HAMIL DI UPTD PUSKESMAS CINERE KOTA DEPOK AGUSTUS TAHUN 2022 - Tri Putri Hardianti (Journal of Midwifery Tiara Bunda, 2023)
The World Health Organization (WHO) reported that there are 52% of pregnant women who experience anemia in developing countries. The purpose of this study was to determine the relationship between Knowledge, Age, Parity, Pregnancy Distance, and Compliance in consuming Fe tablets. This research is an analytic study with a cross sectional design, which is one type of observational study to determine the relationship between risk factors and disease. From the conclusion we can say that cross-sectional research is, among others, descriptive research with analytical research From the results of the chi-square statistical test, it was found that the Knowledge factor p-value was 0.135 where the P-value > 0.05 was the age factor 1. 00 p-value where the p-value was > 0.05, meaning that there is no relationship between knowledge and age with anemia in pregnant women. The chi-square statistical test found the results of the parity factor p-value of 0.047 where the p-value <0.05, the pregnancy distance factor p-value 0.008 where the p-value <0.05, the consumption factor of the FE Tabket p-value 0.037 where the p-value <0.05 means that there is a relationship between parity, pregnancy interval, and adherence to consuming FE tablets with anemia.